Onaanvaarbare verskeidenheid in Galasiers: έκκλησία en συνγωγη 1 - Botma, M. A. (Hervormde teologiese studies, 2000)
Unacceptable diversity in Galatians: έκκλησία and συνγωγη. This article proceeds from the thesis that the formula έν Χριστώ forms the basisof Pauline ecclesiology. To be "in Christ" means to participate in the "Sache Jesu". Participation also means that the believer becomes part of the church. From this thesis the problem of unity and diversity in Galatians is argued. According tot Galatians 2:1-14 it is clear that the "Sache Jesu" was interpreted in diverse ways. The diverse interpretations gave way to conflict between Christian parties. The Christians in Antioch did not follow the Jewish law. Their opponents however felt that it was imperative to hold to circumsicion and the Jewish law. Itis argued that the term έκκλησία was chosen against the term συνγωγη because of the latter term's affiliation with Christians who held to the Jewish law.